Pelatihan Pemasaran Digital Produk Scrunchie Berbahan Limbah Kain Perca untuk Meningkatkan Kompetensi Kewirausahaan - Durahman Marpaung; Adetia Azmi Tanjung; Rahmawani; Hajar Affiah (STIE Bina Karya, 2026)
Digital marketing skills are an important competency for aspiring entrepreneurs in the digital economy. Members of the Entrepreneurship Student Activity Unit (UKM) at Muhammadiyah Asahan University had previously received training on utilizing waste fabric scraps to create economically valuable scrunchies, but still faced limitations in marketing their products. This community service activity aims to improve students' entrepreneurial competencies through digital marketing training for scrunchie products made from waste fabric scraps. The activity was held on May 12, 2026, in the Muhammadiyah Asahan University Hall, involving 44 sixth-semester students from the Management Study Program and the Accounting Study Program who are members of the Entrepreneurship Student Activity Unit. The methods used included socialization, demonstrations, practice, and evaluation. The material provided covered digital marketing concepts, the use of social media and marketplaces, product photography techniques, digital catalog preparation, promotional content creation, and branding strategies. The results of the activity showed that all participants followed the training well and were able to create digital marketing accounts, produce more attractive product photos, compose product descriptions, and create simple promotional content ready for publication on social media. This training successfully improved participants' understanding and skills in utilizing digital technology as a means of product marketing. Thus, this activity contributes to improving students' entrepreneurial competencies while expanding marketing opportunities for scrunchie products made from waste fabric as a sustainable creative business.